The War of Diponegoro: Causes, Strategies, and Impact on Indonesian Politics, Socio-Culture, and Economy - Isnaeniah, Risma Wati; Sulistyadi, Edy; Prasetyo, Heru (Jurnal Multidisiplin Madani, 2024)
The Diponegoro War is one of the most important events in Indonesian history as it marked the beginning of the increasingly strong Dutch colonization of Indonesia. Various general and specific factors between Prince Diponegoro and the Dutch triggered this conflict. Although this war lasted a very short period of 5 years (1825-1830), it caused enormous losses, namely around 200,000 Javanese people lost their lives, almost a quarter of the island of Java was badly damaged, 8,000 European troops were killed, 7,000 Indonesian troops were killed and the costs of the war incurred by the Dutch reached around 20 million guilders. In Addition, the impact of the Diponegoro War was very significant for the people of Central Java, especially in social, economic, and political terms. This research aims to dig deeper into the history of The Diponegoro War and review various aspects related to this war, including the background, tactics, and strategies of the war, as well as the impact of the war on politics, social and economy on the people of Jawa and Indonesian. This research uses a historical approach that focuses on past events. Although the Dutch won the Diponegoro War, it marked the beginning of Indonesia's independence struggle against Dutch colonialism. It showed that the Indonesian people had the spirit and determination to gain independence from foreign colonialism